Differences in Alzheimer’s Disease and Related Dementias Pathology Among African American and Hispanic Women: A Qualitative Literature Review of Biomarker Studies - Royse, Sarah K.; Cohen, Ann D.; Snitz, Beth E.; Rosano, Caterina (Frontiers in Systems Neuroscience, 2021)
Introduction: The population of older adults with clinical diagnosis of Alzheimer’s disease and Related Dementias (ADRD) is growing larger and more diverse. Prevalence of ADRD is higher in African American (AA) and Hispanic populations relative to non-Hispanic whites (nHW), with differences even larger for women compared to men of the same race. We sought to determine if AA and Hispanic women exhibit worse ADRD pathology compared to men of the same race and nHW women. We hypothesized that such differences may explain the discrepancy in ADRD prevalence. Methods: We evaluated 932 articles that measured at least one of the following biomarkers of ADRD pathology in vivo and/or postmortem: amyloid-beta (Aß), tau, neurodegeneration, and cerebral small vessel disease (cSVD). Criteria for inclusion were: 1) mean age of participants > 65 years; 2) inclusion of nHW participants and either AA or Hispanics or both; 3) direct comparison of ADRD pathology between racial groups. Results: We included 26 articles (Aß=9, tau=6, neurodegeneration=16, cSVD=18), with seven including sex-by-race comparisons. Studies differed by sampling source (e.g. ADRC, population), multivariable analytical approach (e.g. adjusted for risk factors for AD), and cognitive status of participants. Aß burden did not differ by race or sex. Tau differed by race (AA